(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article presents the results of a study that aims to explore students’ preference for sport activities on campus. Based on a theoretical analysis of scientific publications, the preferences of modern youth for sports activities and possible proposals for their implementation on campus were identified. A survey was conducted among 1688 students of Stavropol State Agrarian University. Based on this survey, the conditions that affect the involvement of young people in sport activities on campus were identified using statistical procedures of factor analysis. The circumstances that cause students to skip sport activities were also identified. The data obtained during the empirical part of the study allows for informed planning of the development of sports activities on university campus. A research strategy and methodological tools were developed that allow us to study the possibility of implementing sports activities in municipal educational institutions, and in organizations of higher and secondary vocational education.